The gut microbiota in osteoporosis: dual roles and therapeutic prospects - Xie, Xingwen; Liu, Hao; Wan, Kangwei; Li, Jiawen; Qi, Peng (Frontiers in Immunology, 2025)
Recent advances in bone biology have underscored the essential role of the gut microbiota in maintaining skeletal homeostasis. Gut-derived metabolites, particularly short chain fatty acids and tryptophan derivatives, influence bone metabolism through modulation of immune signaling, inflammation, and endocrine networks. Emerging evidence indicates that these effects are context dependent and dose dependent, rather than uniformly beneficial or detrimental. For instance, butyrate and lipopolysaccharide exhibit biphasic effects on both osteogenesis and osteoclastogenesis, contingent on concentration, immune status, and the local microenvironment. Microbiota-targeted strategies such as probiotics, prebiotics, and fecal microbiota transplantation are under active investigation as innovative interventions for osteoporosis in both preclinical and clinical contexts. However, substantial knowledge gaps persist, including inconsistent therapeutic outcomes, limited mechanistic insight into host–microbiota interactions, and the absence of standardized microbial intervention protocols. In addition, safety concerns related to FMT, particularly in immunocompromised elderly populations, emphasize the need for rigorous donor screening, extended follow-up periods, and personalized risk and benefit assessment models. To advance the field, future studies should incorporate multi-omics platforms and precision medicine tools to identify key microbial targets and enhance therapeutic efficacy. This review consolidates current evidence and proposes a conceptual framework to clarify the context-specific roles of the gut microbiota in bone remodeling. A deeper mechanistic understanding will be crucial for translating microbiota-based strategies into safe and effective treatments for metabolic bone disorders.